Implementasi Layanan Bimbingan dan Konseling dalam Pembentukan Karakter Siswa di SMPIT Miftahul Falah Karawang - Ayu Widia Ningsih; Hendri Asri Harahap; Ariq Wicaksono; Fuad Shofwan; Nur Aini Farida (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the implementation of guidance and counseling services at SMPIT Miftahul Falah Karawang, focusing on the counseling approaches applied and the challenges faced by counseling teachers during the process. The research employed a qualitative descriptive method using observation and interviews as data collection techniques. The results reveal that guidance and counseling services are carried out through a humanistic and persuasive approach grounded in Islamic values. The counseling teacher serves as a facilitator who understands students’ emotional conditions and guides them toward behavioral improvement based on awareness and responsibility. This approach creates a supportive environment that encourages openness and mutual trust between the teacher and students. Nevertheless, several challenges remain, including the limited number of counselors, students’ varying levels of openness, and insufficient coordination among teachers in addressing student issues. These findings highlight the importance of institutional support through the enhancement of human resources, continuous professional development, and stronger collaboration between counseling teachers and school administrators. Such efforts are expected to strengthen the role of guidance and counseling services as a medium for character education in accordance with Islamic principles.